PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATERI GETARAN DI MTSN 5 TULUNGAGUNG - Nur Faizah Amilia; Muhammad Luqman Hakim Abbas; Kurniawan, Husni Cahyadi; Gaguk Resbiantoro (JEAS (Journal of Educational and Applied Science), 2023)
The purpose of this study was to find out the effect of the Problem Based Learning Model with mind mapping assistance on students' critical thinking skills on vibration material at MTsN 5 Tulungagung, and to determine the effect of the Problem Based Learning Model with mind mapping assistance on critical thinking skills on vibration material at MTsN 5 Tulungagung. This study uses a quantitative approach with a type of quasi-experimental research. The design form used is Pretest-posttest control group design, with class selection using cluster random sampling technique.  Data collection techniques using tests and documentation. The results of this study indicate that there is an effect between the Problem Based Learning learning model assisted by mind mapping on students' critical thinking skills on Vibration Material class VIII MTsN 5 Tulungagung with the acquisition of sig. (2-tailed) 0.00 <0.05 with the effect of the Problem Based Learning learning model assisted by mind mapping on the critical thinking skills of students in the Vibration Material of class VIII MTsN 5 Tulungagung of 0.7 or 76% classified as medium.